Dinamika Psiko-Sosial dalam Pendidikan Kesetaraan: Studi Pemenuhan Kebutuhan Dasar Psikologis - Rofi'atunnisa; Juntika Nurihsan; Tina Hayati Dahlan (Jurnal Riset Sosial Humaniora dan Pendidikan, 2026)
The ups and downs of learner participation in learning activities at Pusat Kegiatan Belajar Masyarakat (PKBM) is not only influenced by technical factors, but is also closely related to how they interpret their learning experiences. Through the lens of Self-Determination Theory, this study explores the urgency of fulfilling basic psychological needs—namely autonomy, competence, and relatedness—to maintain and increase learning motivation. This research uses a phenomenological approach to explore the subjective experiences of three school-age learners in the Equivalency Education program, Paket C. Through in-depth interviews, it was found that environmental support for the fulfillment of learners' basic psychological needs varies greatly. The quality of social interaction in the PKBM environment proved to be key; warm, open, and consistent interpersonal support was able to encourage more authentic learning engagement. These findings underscore that PKBM is not merely an academic space, but a crucial social ecosystem in facilitating basic psychological needs, which ultimately determine learners' intrinsic motivation and perseverance in learning.